Android mobile malware classification using tokenization approach based on system call sequence - Ahmad I.N.; Farida Hazwani Mohd Ridzuan; Madihah Mohd Saudi; Sakinah Ali Pitchay; Nurlida Basir; Nur Fatin Nabila Mohd Rafei Heng (Newswood Limited, 2024)
Indexed by SCOPUS